2017
DOI: 10.1016/j.jet.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

On public good provision mechanisms with dominant strategies and balanced budget

Abstract: Consider a mechanism for the binary public good provision problem that is dominant strategy incentive compatible (DSIC), ex-post individually rational (EPIR), and ex-post budget balanced (EPBB). Suppose this mechanism has the additional property that the utility from participating in the mechanism to the lowest types is zero for all agents. Such a mechanism must be of a threshold form, in which there is a fixed threshold for each agent such that the public good is not provided if there is an agent with a value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…From 7, we see that that for all integers α less than (respectively, larger) values than the optimal, the welfare will be increasing (respectively, decreasing) in α. Thus, we have shown that in both cases (1) and 2…”
Section: Expected Welfare and Optimal Quota With Fixed Nmentioning
confidence: 52%
See 1 more Smart Citation
“…From 7, we see that that for all integers α less than (respectively, larger) values than the optimal, the welfare will be increasing (respectively, decreasing) in α. Thus, we have shown that in both cases (1) and 2…”
Section: Expected Welfare and Optimal Quota With Fixed Nmentioning
confidence: 52%
“…In the USA there has been a significant growth of direct public initiatives at the state and local level as described in [15], [16] and [17] and with it an increased use of "direct democracy" for decisions on public projects. Such decisions relate to sports stadiums, highway construction, public transportation, flood control, For instance in [1], this threshold is characterized for a budget balanced mechanism satisfying ex-post individually rationality and incentive compatibility. The theoretical literature studies mechanisms under which honest revelation is an equilibrium strategy.…”
Section: Introductionmentioning
confidence: 99%
“…We also give a sufficient condition on the distribution of types such that the only ex post individually rational, ex post budget balanced, and DSIC mechanism immune to D‐blocking is a posted price mechanism. D‐blocking is accomplished using a non‐negative spread mechanism 5 Kuzmic and Steg. (2017) gave a characterization of such mechanisms.…”
Section: Vulnerability To D‐blockingmentioning
confidence: 99%
“…The level of the prosperity depends on the soundness of budget strategies, including budget balance (Kuzmics & Steg, 2016). The definition of financial prospects simplifies the procedure of approval of the annual budgets and improves the efficiency of the fiscal adjustment mechanism (Bič, 2012;Jakš, 2006).…”
Section: Literature Used For Researchmentioning
confidence: 99%